2D multiresolution automated system for detecting BSRs on seismic reflection images. (20th July 2018) - Barba-Rojo, Perla Karina; Solorza-Calderón, Selene; González-Fernández, Antonio; González-Escobar, Mario
Abstract: This work presents an automation system for detecting the presence of bottom-simulating reflectors (BSRs) and other reflectors parallel to the sea bottom in real seismograms. The system uses automatic gain control to aid the thresholding method for edge detection and segmentation to calculate the sea bottom curve. After preprocessing the seismic reflection images, 2D multiresolution analysis methodology was used to develop the automated pattern recognition system which detects BSRs and other parallel reflectors in a robust manner. Synthetic and real seismic images were used to evaluate the proposed methodology, which showed excellent results in both cases.